2010
DOI: 10.1002/erv.1066
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and eating in binge eating disorder and obesity

Abstract: This study compares 20 binge eaters (BED), 23 obese patients (OB) and 20 normal weight controls (CO) with regard to everyday emotions and the relationship between emotions, the desire to eat and binge eating. Modified versions of the Differential Affect Scale and Emotional Eating Scale were used and the TAS-20 and Symptom-Check-List-27 administered to assess overall psychopathology and alexithymia. BED-subjects show a more negative pattern of everyday emotions, higher alexithymia scores and the strongest desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 55 publications
(63 reference statements)
9
112
1
4
Order By: Relevance
“…More recently, researchers have found that anger, feeling hurt by others, feeling disappointed, sadness and feeling guilty were associated to binge eating, suggesting that emotional eating may be related to a wide range of negative emotions and problematic interpersonal relationships [113]. This is in line with research that has suggested that people with eating disorders are often highly sensitive to social threat and rejection [114,115].…”
Section: What Role Does Emotional Eating Have In the Development Of Cmentioning
confidence: 84%
“…More recently, researchers have found that anger, feeling hurt by others, feeling disappointed, sadness and feeling guilty were associated to binge eating, suggesting that emotional eating may be related to a wide range of negative emotions and problematic interpersonal relationships [113]. This is in line with research that has suggested that people with eating disorders are often highly sensitive to social threat and rejection [114,115].…”
Section: What Role Does Emotional Eating Have In the Development Of Cmentioning
confidence: 84%
“…It was found that there was a positive correlation between food addiction and depression scores as well as food addiction and body mass index (BMI measures body fat depending on height and weight). Additionally, Zeeck et al (2010) found out that, feelings of loneliness, disgust, extreme fatigue and shame lead to binge eating behavior. Southward et al (2014) conducted a study in order to find if loneliness mediates the relationship between emotion dysregulation and bulimia nervosa/binge eating.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…In addition, according to Macht, several of the studies reviewed reinforce the idea that most people report changes on eating (eat more or eat less) in response to emotional stress, as well as that negative emotional states in daily life can be associated with a tendency to eat as an emotion regulation strategy not only in restrained eaters and binge eaters, but also in normal eaters. Zeeck et al (2011) developed a study in which they explored the relationship between emotional experiences and eating. Their results suggest that anxiety has a minor importance in the context of eating when compared to other emotions, especially emotions related to interactions with others (e.g.…”
Section: Obesity and Emotional Regulationmentioning
confidence: 99%